FOSTERING THE DEVELOPMENT OF CRITICAL THINKING SKILLS IN STUDENTS (International journal of artificial intelligence, 2024)
This article discusses the necessity of fostering the development of critical thinking among students in order to further enhance the quality of education in Uzbekistan. It emphasizes the importance of enriching their knowledge from an early age, guiding them towards independent thinking, and encouraging creative freedom.